2018
DOI: 10.1111/nph.15361
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the primacy of living root inputs, not root or shoot litter, in forming soil organic carbon

Abstract: Soil organic carbon (SOC) is primarily formed from plant inputs, but the relative carbon (C) contributions from living root inputs (i.e. rhizodeposits) vs litter inputs (i.e. root + shoot litter) are poorly understood. Recent theory suggests that living root inputs exert a disproportionate influence on SOC formation, but few field studies have explicitly tested this by separately tracking living root vs litter inputs as they move through the soil food web and into distinct SOC pools. We used a manipulative fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
153
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(183 citation statements)
references
References 66 publications
8
153
1
1
Order By: Relevance
“…It is also consistent with the few studies that compared SOM formation from root and shoot residues. Contribution to SOM formation from roots is often found to be much higher than from leaves (Berhongaray, Cotrufo, Janssens, & Ceulemans, 2018;Sokol et al, 2018), but leads to higher POM or POM like fractions (Bird et al, 2008), while leaf litters often exhibit a relatively higher contribution to MAOM or persistent SOM fractions (Hatton, Castanha, Torn, & Bird, 2015;Lavallee et al, 2018). While supporting the idea that more SOM can be formed from root residues in annual crops where they often have a higher recalcitrance than above-ground residues, these findings suggest that the mean residence time of root residuesderived SOM is not higher than that formed from above-ground residue decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also consistent with the few studies that compared SOM formation from root and shoot residues. Contribution to SOM formation from roots is often found to be much higher than from leaves (Berhongaray, Cotrufo, Janssens, & Ceulemans, 2018;Sokol et al, 2018), but leads to higher POM or POM like fractions (Bird et al, 2008), while leaf litters often exhibit a relatively higher contribution to MAOM or persistent SOM fractions (Hatton, Castanha, Torn, & Bird, 2015;Lavallee et al, 2018). While supporting the idea that more SOM can be formed from root residues in annual crops where they often have a higher recalcitrance than above-ground residues, these findings suggest that the mean residence time of root residuesderived SOM is not higher than that formed from above-ground residue decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…This conflicts with Rasse, Rumpel, and Dignac (2005), who found that the mean residence time of rootderived C in soils is 2.4 times greater than shoot-derived C, and Jackson et al (2017) as likely to be stabilized as SOM, perhaps higher in agricultural systems. Indeed, this study only investigated residues inputs, and root exudates given their inherent lability may efficiently form persistent SOM (Cotrufo et al, 2013;Sokol et al, 2018;Strickland, Wickings, & Bradford, 2012). We believe that the fractionation of SOM into physical fractions of known stabilization mechanisms can help predict the persistence of residue derived C and N in soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in root exudation has spiralled with the realization of its importance in plant nutrient uptake (Mommer et al , ) and the formation of stable soil organic C (Sokol et al , ). In addition, root exudates form a direct communication pathway between plants and rhizosphere microbes and have the potential to influence plant tolerance and survival during severe abiotic stress.…”
Section: Introductionmentioning
confidence: 99%